PENGARUH KOMPONEN ARUS KAS, LABA BERSIH, UKURAN PERUSAHAAN, DAN RETURN ON ASSET TERHADAP RETURN SAHAM - Ayuandani Dwi Purnama Sari, 12.05.52.0124; Puspitasari, Elen (Students' Journal of Accounting and Banking, 2016)
This study aimed to determine and to analyze the effect of cash flows from operating, investing, and financing, net income, company size, and return on asset to stock return on manufacturing companies in Indonesia Stock Exchange.The period used in this study at 20122014. Observasional data used in this study is 114. The sampling method using purposive sampling. The relation between variables is described by using multiple regression analysis. Net income proxied by return on asset. Based on the test results SPSS revealed that there is a positive and significant simultanuous effect between cash flows from operating, financing, and net icome of stock returns. While the variable cash flows of investment and company size turned out to haven’t effect on stock returns. Keywords: Components of Cash Flows, Net Income, Company Size, Stock Returns